Traços de compaixão e misericórdia na história do Pará: instituições para meninos e meninas desvalidas no século XIX até início do século XX - Sousa, Celita Maria Paes de (2010)
The present study aims to investigate the history of the institutions for disfavored boys and girls from the current State of Pará (Brazil), considering the period starting in the beginning of the XIX century up to 1912, in the beginning of the XX century. The temporal limits can be justified by the foundation of the first institution for caring disfavored girls, named Casa das Educandas [House of Students] or Recolhimento das Educandas [Shelter of Students], in 1984, and the ending of an economic period, named Rubber Cycle (1870 to 1912). This cycle promoted great urban, cultural, and political changes in the Amazon region due to the surplus derived by the rubber economy. The outcomes from that amazing cycle of economic accumulation in the capital of the State, Belem, draw a period known as Belle Époque. That time appear the most structured institutions for caring disfavored girls and boys. Among the more important, the first opened for attending boys, in 1872, was Instituto de Educandos Artífices do Pará [The Carftsman Student Institute of Pará]. In 1897, it became The Lauro Sodré Institute. In the same year, came the second institution, this time for girls, the Gentil Bittencourt Institute. The research coverers institutions whose attended girls and boys, but the emphasis was placed on institutions for disfavored girls. In the same way, the research focus on the period during the institution enrollment and engagement, placing less attention to the period that precedes that. The methodology encompassed, initially, bibliography review, related to the period considered, referred to the history of disfavored childhood, and institutions for disfavored boys and girls in the State of Pará, and other states of Brazil. Primary and secondary sources were studied in the Sector of Rare Books and Documents of Arthur Vianna Library, and in the Public Archives of Pará, and also in the Biblioteca da Santa Casa Paraense [Holy House of Pará Library]. All of them placed in Belém (Brazil). The study considered books, journals, newspapers, but the emphasis (and therefore the time consumed) was placed on reading and analyzing official documents, prioritizing: reports, messages, speeches, and other types of communications from the provincial government, and later State, do Pará. The studied material was photographed, or digitized or even hand copied. The study shows that, in the beginning, the religious orders were dominant on founding and maintaining the institutions for disfavored girls. The state public actions related to attending disfavored girls and boys only started in the end of XIX century, driven from the economic and social changes that emerged as a consequence of the new republican state. That new model postulated that the progress of the nation derived from education and instruction